THE ALTAMIRO DE MOURA PACHECO STATE PARK – PEAMP IN THE CONTEXT OF THE OCCUPATION OF MATO GROSSO GOIANO (CIPEEX, 2022)
The Cerrado occupies about 25% of Brazilian territory (CBC/ICMBio, 2022). It is the second largest biome in the country, surpassed in area only by the Amazon. It is home to important natural resources, as well as global economic interests, given the scale of agribusiness, an economic activity responsible for a large part of the economic development of the Brazilian Midwest, generating improvements in the infrastructure of the States and producing food on a large scale, even though the variety of products is limited. It is in this duality that the concern for the conservation of the Cerrado has been growing, both in the academic community and in society at large.In the context of natural resource conservation, the development of public policies for this purpose is essential, as well as the enforcement of current environmental legislation. In this sense, among the public policy mechanisms related to the area of environmental conservation, we have Conservation Units – CUs, especially those with full protection.This work (dissertation in progress at the PPGSTMA of UNIEVANGÉLICA) aims primarily to research the creation of the Altamiro de Moura Pacheco State Park - PEAMP, a Full Protection Conservation Unit managed by the State of Goiás, located along the BR-153, near the state capital, as well as to analyze its current landscape and discuss its importance for the environmental conservation of the Cerrado, especially in the context of the Environmental History of Goiás and the region of Mato Grosso de Goiás – MGG.The PEAMP was created by State Law No. 11,878 on December 30, 1992. It is located in the watershed of the Ribeirão João Leite, adjacent to the Environmental Protection Area – APA, as well as the João Leite State Park.It is an important remnant of the native vegetation of the MGG region, an extension of forest phytophysiognomy located in the central-southern part of Goiás (Barbosa et al. 2020) that includes, among other municipalities, parts of Goiânia and parts of Anápolis (Giustina et al. 2020).
Keywords: Conservation Units; Cerrado; Sustainable Development